Association of water stress and Fusarium solani exacerbated Dalbergia sissoo dieback disease: Water stress and F. solani exacerbated D. sissoo dieback - Muhammad , Asif Javed; Bilal Zia, Muhammad; Yasin, Ghulam; Naseer, Junaid; Alharbi, Sulaiman Ali; Alfarraj, Saleh; Javed Ansari, Mohammad; Du, Zhenjie; ur Rahman, Shafeeq (Cellular and Molecular Biology, 2024)
Globally, there is a growing concern about tree mortality due to harsh climates and changes in pest and disease patterns. However, experimental studies on the interactions between biotic and abiotic stresses in plants are relatively scarce. In this study, we investigated the interaction between Fusarium solani and water-stressed Dalbergia sissoo saplings. We postulated that under drought conditions, sissoo plants would become more susceptible to dieback infestation. Five fungi, including Fusarium oxysporum, Curvularia lunata, Cladophialophora carrionii, Alternaria alternaria, and Fusarium solani, were isolated from an old shisham tree showing advanced symptoms of dieback infestation. These fungi were identified based on their ITS sequence homology and spore characteristics. Dieback development was more pronounced in plants experiencing water stress, regardless of their predisposition or whether it occurred simultaneously. Lesions were more noticeable and longer in predisposed saplings (3.8cm), followed by simultaneous (2.4cm) and much smaller lesions in seedlings that were inoculated and well-watered (0.24cm). Progressive browning of the upper leaves, which lowers sapling height in predisposed, simultaneous, and well-watered inoculated saplings to 8.09 inches, 5.93 inches, and 17.42 inches, are typical dieback symptoms. Water stress causes the loss of chlorophyll a, b, and carotenoids, which reduces stomatal conductance, transpiration rate, and photosynthetic activity, leading to poor development and mortality. Similarly, predisposed, simultaneous, and well-watered inoculated seedlings expressed increased activity of CAT (22.57, 18.148, and 9.714 U/mg) and POD (3.0, 4.848, 1.246 U/mg), to reduce the damage caused by elevated levels of H2O2 expression. It is concluded that water stress is the main cause of dieback in shisham saplings that subsequently disposed of infected seedlings to secondary agents such as fungi and insects in the advanced stages of the dieback with prolonged drought stress. The lack of dieback in native populations is attributed to the absence of several ecological stresses, including water stress, extended droughts, waterlogging, and salinity. This study emphasizes the need for additional research into the effects of abiotic factors linked with fungal diseases on the long-term production and management of D. sissoo in Pakistan.